Komunikasi Virtual Dalam Game Online Counter-Strike 2 Sebagai Media Pembelajaran Bahasa Inggris - Darmawan, Aditya; Haryadi Mujianto; Resty Mustika Pratiwi (Jurnal Spektrum Komunikasi, 2024)
This research is motivated by the rise of people who play online games, one of which is the online game Counter-Strike 2, which is favored by the world community. Playing Counter-Strike 2 online games can be used as a medium of learning English because, in Counter-Strike 2 online games, you can communicate with the international community using English. People can improve their English language skills through the experience they get when communicating virtually with the global community by playing Counter-Strike 2 online games. The purpose of this study is for people to take advantage of Counter-Strike 2 online games, not just entertainment media so that they can use them to communicate virtually with the international public as a medium of learning and honing skills in English. This study uses a descriptive method with a qualitative approach. Data collection techniques used by researchers are interviews, observations, and literature studies. The results of this study show that playing the online game Counter-Strike 2 can be used as a medium of learning English. This is due to the player's habit of communicating with each player using the international language, namely English, when the game starts. Learning English through Counter-Strike 2 online games can add new knowledge that does not exist in formal education or books. Namely, we can learn new terms in English, known as slang. If you are used to communicating with the international public, it can increase your confidence in using English.